2014
DOI: 10.3892/or.2014.3103
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Inonotus obliquus inhibits migration and invasion in B16-F10 cells by suppressing MMP-2 and MMP-9 via downregulation of NF-κB signaling pathway

Abstract: Polysaccharides derived from Inonotus obliquus (PIO) are known to possess multiple pharmacological activities including antitumor activity. However, the possible molecular mechanisms of these activities are unknown. In the present study, we determined the anti-metastatic potential and signaling pathways of PIO in the highly metastatic B16-F10 mouse melanoma cell line in vitro. We found that PIO suppressed the migration and invasive ability of B16-F10 cells and decreased the expression levels and activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…MMPs are partly mediated by the mitogen‐activated protein kinase (MAPK) pathway an MAPK pathway plays a central role in regulating the expression of MMP‐2 and MMP‐9 . MAPK pathway regulated various cellular activities such as proliferation, invasion, metastasis, and death . NK and c‐Jun are the factors of MAPK, here, results indicated that TET decreased p‐JNK and p‐c‐Jun in GBM 8401 cells (Figure C) which means TET suppressed MAPK signal pathway in GBM 8401 cells.…”
Section: Discussionmentioning
confidence: 76%
“…MMPs are partly mediated by the mitogen‐activated protein kinase (MAPK) pathway an MAPK pathway plays a central role in regulating the expression of MMP‐2 and MMP‐9 . MAPK pathway regulated various cellular activities such as proliferation, invasion, metastasis, and death . NK and c‐Jun are the factors of MAPK, here, results indicated that TET decreased p‐JNK and p‐c‐Jun in GBM 8401 cells (Figure C) which means TET suppressed MAPK signal pathway in GBM 8401 cells.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, inhibition of p-p38, p-ERK1/2 and p-JNK1/2 all markedly attenuated MMP-9 expression in 2-CE exposed astrocytes, suggesting that all three kinds of MAPK signal pathways were activated, and collectively involved in modulation of MMP-9 expression in 2-CE exposed astrocytes. Until now, there is a large body of evidence to suggest that MMP-9 expression is regulated by p38, ERKs and JNKs in different cell types (Lee et al, 2014; Kim et al, 2015; Lian et al, 2015). However, as far as we know, this is the first time to discuss the molecular mechanisms of MMP-9 expression regulation in astrocytes exposed to 2-CE.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin was also observed to inhibit the invasion of EC cells at non-cytotoxic concentrations. MMP-2 and -9 play a significant role in the metastasis of tumor cells (14)(15)(16). By degrading the ECM, MMP-2 and -9 make the metastasis of tumor cells possible.…”
Section: Discussionmentioning
confidence: 99%